2022
DOI: 10.1021/acs.jpcc.2c00090
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Slow Diffusion of Gold Nanoparticles under Confinement in Mesoporous Silica

Abstract: We report an X-ray photon correlation spectroscopy (XPCS) study of the mobility of colloidal gold nanoparticles with a diameter of approximately 4 nm in glycerol under confinement within the channels of SBA-15 mesoporous silica with pore diameters of approximately 6 and 12 nm. The XPCS correlation functions result from an effective heterodyne signal due to the mixing of the coherent scattering from the nanoparticles and the mesoporous silica. Over the range of wave vectors and hence length scales probed, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This effect, together with the loss of electrosteric properties of PEG ligands due to conformational changes upon solidification, can result in aggregation. It should be noted that AuNR diffusion is still possible when ethanol is solidified, considering previous observations that AuNR can diffuse in liquid crystals and even in mesoporous silica . Grain boundaries are expected to be preferred sites for aggregation because these regions are the last ones to transit from liquid ethanol to solid ethanol, during the solidification process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect, together with the loss of electrosteric properties of PEG ligands due to conformational changes upon solidification, can result in aggregation. It should be noted that AuNR diffusion is still possible when ethanol is solidified, considering previous observations that AuNR can diffuse in liquid crystals and even in mesoporous silica . Grain boundaries are expected to be preferred sites for aggregation because these regions are the last ones to transit from liquid ethanol to solid ethanol, during the solidification process.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that AuNR diffusion is still possible when ethanol is solidified, considering previous observations that AuNR can diffuse in liquid crystals 30 and even in mesoporous silica. 31 Grain boundaries are expected to be preferred sites for aggregation because these regions are the last ones to transit from liquid ethanol to solid ethanol, during the solidification process. The observed AuNR aggregation constitutes clear evidence of AuNR diffusion in solidified ethanol and suggests diffusion processes of PEG-capped AuNR in solid solvents, a process most often ruled out in the realm of nanoscience and nanotechnology.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorbates under confined conditions were shown to exhibit different properties compared to their corresponding bulk phases, such as miscibility, phase transitions, and diffusion 12 . Many studies have revealed that diffusion under confinement will be more than an order of magnitude slower than in the bulk phase [13][14][15] , demonstrating that strong confinement will always be accompanied by slow diffusion. Although the diffusion and mass transfer performance of porous materials will significantly affect their catalytic efficiency and selectivity 8 , no efficient solutions are currently available to obtain rapid diffusion in strongly confined spaces (especially for bulky or long-chain molecules).…”
mentioning
confidence: 99%